Pengaruh Pembiayaan Terhadap Profitabilitas Bank Syariah Indonesia (Studi Kasus Ex BSM KC Demang Palembang Periode 2016-2020) - Lidya Pisatiya Asih; Fadilla Fadilla; Meriyati Meriyati (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2021)
This study was conducted to determine the effect of mudharabah, musyarakah, and murabahah financing on the profitability of Indonesian Islamic Banks Case Study Ex BSM KC Demang Palembang Period 2016-2020. The purpose of this study is to analyze the effect of mudharabah, musyarakah, and murabahah financing on the profitability of Indonesian Islamic Banks Case Study Ex BSM KC Demang Palembang period 2016 - 2020 either partially or simultaneously. The method used in this research is quantitative. Analysis of the data used is multiple linear regression analysis. The results showed that: (1) mudharabah financing had a negative and insignificant effect on ROA, (2) musyarakah financing had a positive and significant effect on ROA, (3) murabahah financing had a negative and insignificant effect on ROA. (4) Mudharabah, musyarakah, and murabahah financing have a positive and significant effect on profitability (ROA).